The Handling System of Product and Existence of Waste Components in Fishing Operation of Tuna in Bitung, North Sulawesi - Mustaruddin Mustaruddin; Joko Santoso; Mulyono Baskoro (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Handling in fishing vessel is urgent to maintaining the quality of tuna products, while the existenceof waste components can bother the performance of fishing operations. The aims of this research are toevaluate the handling system of tuna products in fishing vessel and to analyze the influences of fishingoperation to the existence of waste components. This research methods are no control chart and regressionmodel approach. Research result shows that the handling system in the fishing operation of tuna in Bitungis not optimum. But the quality of tuna products which landed is still in controlled as shown by amountof rejecting products in UCL-LCL range (0 – 3,63 reject products/processing). The influence of amount oftuna caught per setting (X) to existence of bait waste (Y) formulated with model Y = - 1,176X+37.794, theinfluence of amount of tuna products (X) to the existence of ices remained Y) formulated with model Y =- 0,002X + 62,226, and also the influences of fishing operation which deputized by the amount of ABK (X1)and number of operating days (X2) to the existence of freshwater remained (Y) formulated with model Y= 50,000X1-23,704X2+288,889. The significant impacts are only the influence of amount of tuna productsin existence of ices remained (sigh = 0,036) and number of operating days of the existence of freshwaterremained (sigh = 0,037).Keywords: Bitung, waste components, handling system, tuna